PENGARUH PENGAWASAN, KOMPENSASI FINANSIAL, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. MITRA BUMI KABUPATEN KAMPAR - Rizka Audina; Nuryanti '; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted at PT. Mitra Bumi Kabupaten Kampar. With the aim to identify and analyze the influence of Influence Supervision, Financial Compensation and discipline on labor productivity at PT. Mitra Bumi Kabupaten Kampar. Population is the whole object to be examined. Where in this study population was all employees of PT. Mitra Bumi Kabupaten Kampar. The number of employees is 113 people. Determination of the number of samples using census method by setting it to 113 employees as respondents and data processing using multiple linear regression. Based on the test results if the data using multiple linear regression can be drawn some conclusions, namely: supervision, financial compensation and working discipline simultaneously affect the productivity of employees at multiple linear regression. Supervision partial effect on the productivity of employees at multiple linear regression. Financial compensation is partially affected the productivity of employees at multiple linear regression. Labor discipline partial effect on the productivity of employees at multiple linear regression. Expected to companies in order to increase productivity of employees. For example, by giving motivation regarding bonuses, big salary, and other benefits for employees who work in earnest. Thus increasing employee productivity.Keywords: Monitoring, Compensation, Discipline and productivity.